FIRST PRINCIPLE DESIGN LOAD ESTIMATION FOR LH2 FUEL TANKS BY MEANS OF 0D APPROACH - OMAE Data Set - Lampe, Tobias (Zenodo, 2023)
Supplementary data set for the OMAE publication "FIRST PRINCIPLE DESIGN LOAD ESTIMATION FOR LH2 FUEL TANKS BY MEANS OF 0D APPROACH". Contains the complete set of data for the presented cases while only selected data series are shown in the paper.